BIOLOGICAL STUDY OF PEST INSECT GREEN STINKBUG NEZARA VIRIDULA L. (HEMIPTERA: PENTATOMIDAE) IN THE LABORATORY - Cindowarni, Olivia; Siska, Febriana (Fakultas Sains dan Teknologi, Universitas Islam As-Syafi'iyah, 2023)
Green Stinkbug (Nezara viridula L.) in English is called